A55: Clostridium difficile Infection‐Associated Reactive Arthritis in a Pediatric Cohort. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Horton, Daniel B.; Strom, Brian L.; Putt, Mary E.; Rose, Carlos D.; Sammons, Julia S.
Abstract : Background/Purpose: Clostridium difficile infection (CDI) has increased among children and is associated with significant morbidity and mortality. CDI‐associated reactive arthritis (CDIAReA) has been described in adults and a few pediatric case reports, but little is known about CDIAReA in pediatric patients. Methods: Children ages 2–20 with CDIAReA in 2004–2013 were identified within a multistate pediatric care network's electronic medical record. Administrative data were used to identify cases defined by: 1) a diagnosis code for arthritis and 2) the CDI diagnosis code and/or positive C. difficile test in any setting (ambulatory or inpatient). Records were reviewed to confirm presence of symptomatic CDI and acute arthritis and/or tenosynovitis that met the following inclusion criteria: 1) occurrence between 4 weeks before and 12 weeks after CDI diagnosis, 2) documentation by a physicianlevel provider or imaging, 3) no other cause identified, and 4) negative synovial fluid cultures (if obtained). Results: 111 patients were identified for record review, and 13 met the inclusion criteria. Median age of confirmed cases was 13.2 years [range 3.4, 19.3], with similar sex distribution (6 females, 7 males). Approximately half (46%) of cases had chronic medical conditions, including 3 (23%) with autoimmune diseases, whose underlying condition did not explain their acute arthritis. Among subjects with CDIAReA, all CDIs were community‐associated and mild, except for 1 subject with preexisting lupus nephritis. Arthritis was most often migratory (85%) and polyarticular (54%) involving large and small joints, with a median of 6 affected joints [range 2, 15]. The most commonly involved joints were knees (69%) and ankles (69%) followed by wrists (62%) and elbows (54%). Eight patients (62%) experienced concurrent fever, and 9 (69%) had rash. Over half (62%) were hospitalized due to joint pain. Of these, 5 (38%) were suspected to have septic arthritis and 2 (15%) underwent surgical drainage procedures for presumed septic hip arthritis with purulent effusions (both culture‐negative). Median time from onset of gastrointestinal symptoms to resolution of joint symptoms was 30 days [range 8, 76]. Symptoms generally resolved with treatment of underlying CDI and, in 69%, NSAID use. Three subjects (23%) without prior arthritis had subsequent recurrent episodes of migratory joint pain not associated with documented CDI. Aside from the primary physician, 85% were evaluated by emergency physicians, 69% by rheumatologists, 54% by inpatient pediatricians, and 46% by orthopedists. Of confirmed cases, 5 (38% [95% CI 14, 68%]) were never diagnosed with CDIAReA by their treating providers. Conclusion: CDIAReA is an under‐recognized pediatric condition characterized by a painful, migratory, often polyarticular arthritis of large and small joints in the setting of CDI. Though a self‐limited condition in this cohort, its acuity led to considerable morbidity and resource utilization, in some cases due to confusion with septic arthritis. Further research is needed to determine the incidence and risk factors for pediatric CDIAReA.